Halogen-free flame-retardant master batch, preparation method thereof and high-strength halogen-free flame-retardant injection molding material
Halogen-free flame retardant is solved by using bis(4-carboxyphenyl)phenylphosphine oxide and silane coupling agent in halogen-free flame retardant masterbatches, and by modifying graphene-loaded halogen-free flame retardant, halogen-free flame retardant is solved The problem of insufficient masterbatch performance has achieved improvements in high strength, heat resistance and flame retardancy.
Patent Information
- Application Number
- CN202411467270.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-24
AI Technical Summary
While ensuring flame retardant performance, existing halogen-free flame retardant masterbatches are difficult to maintain the fluidity, processing and mechanical properties of injection molded plastics, and have insufficient heat resistance.
Bis(4-carboxyphenyl)phenylphosphine oxide is used as a chain extender, and combined with diisocyanate and polyol to react to form polyurethane. The silane coupling agent is reacted with epoxy resin to produce a flame retardant carrier, and modified graphite is used to produce a The ene is loaded with halogen-free flame retardant, and the halogen-free flame retardant masterbatch and flame retardant synergist are used in concert to adjust the molar ratio and dosage to improve the melt index, tensile strength, impact strength and heat resistance.
It significantly improves the flowability, processing performance, tensile performance, impact strength and heat resistance of halogen-free flame retardant masterbatches, and at the same time improves the flame retardant performance of injection molding to ensure the overall performance of the material.
Smart Images

Figure CN119177015A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic masterbatches, in particular to a halogen-free flame-retardant masterbatch and a preparation method thereof, and a high-strength halogen-free flame-retardant injection molding material. Background Art
[0002] With the continuous advancement of science and technology and the improvement of people's living standards, the fire resistance of polymer materials has received more and more attention. Flame retardant masterbatch, as a plastic additive with fire resistance, has been widely used in many fields in recent years and plays a vital role. Its good flame retardant properties can effectively reduce the loss in fire and protect people's lives and property. Therefore, as an important additive that can achieve the fire resistance requirements of polymer materials, the performance improvement research of flame retardant masterbatch is particularly important.
[0003] Common flame retardant masterbatches are flame retardant materials made of resin as the main component by adding corresponding flame retardants and other auxiliary additives. Among them, flame retardant materials are mainly halogen flame retardants (including Br and Cl compounds), inorganic non-halogen flame retardants (aluminum hydroxide, magnesium hydroxide, antimony trioxide, etc.) and intumescent non-halogen flame retardant systems (ammonium polyphosphate, zinc borate, etc.). Halogen flame retardants have reduced their application due to their poor thermal stability and environmental performance. Inorganic non-halogen flame retardants and intumescent non-halogen flame retardant systems have the advantages of good flame retardancy and green environmental protection, but their compatibility with organic polymer resins is poor and the amount of flame retardant added is large, which to a certain extent damages the processing performance and physical and mechanical properties of the material.
[0004] There is a problem of poor compatibility between halogen-free flame retardants and PA6 matrix. A lower amount of flame retardant added results in poor flame retardant effect, while a higher amount of flame retardant added makes the fluidity of PA6 material worse. Moreover, its special structural characteristics make it difficult for flame retardants to enter the fully cross-linked rubber-plastic system, making PA6 material difficult to injection mold and affecting the mechanical properties of the injection molded products.
[0005] Patent CN103627168A discloses a halogen-free flame-retardant masterbatch for nylon, including PA6 resin, nitrogen-based flame retardant, primary antioxidant, auxiliary antioxidant, external lubricant and internal lubricant. The prepared masterbatch has good dispersibility. However, PA6 resin is extremely flammable, and the flame retardant properties of the prepared material need to be further improved.
[0006] Patent CN109181156B reports flame-retardant PVC masterbatch and its preparation method, including composite PVC flame-retardant resin, core-shell pigment filler, diphenylmethane diisocyanate, dispersant, methyl trifluoroacetate, plasticizer, anhydrous ethanol, and the flame retardant effect is achieved by grafting siloxane functional groups onto the base resin. However, after excessive addition of flame retardant, the heat resistance is reduced, and the mechanical properties of the material are significantly reduced.
[0007] Increasing the amount of flame retardant added can improve the flame retardant performance, but it may lead to poor fluidity, processing performance and mechanical properties of flame retardant masterbatch. At the same time, the masterbatch has poor compatibility with the base material during the injection molding process, which reduces the strength and flame retardant properties of the injection molding material. The addition of volatile flame retardants reduces the heat resistance of the injection molding material. How to maintain other properties of the injection molding material while ensuring flame retardant properties is a key issue that needs to be solved in the research and development of halogen-free flame retardant masterbatch.
[0008] To this end, a halogen-free flame-retardant masterbatch and a preparation method thereof and a high-strength halogen-free flame-retardant injection molding compound are proposed. Summary of the invention
[0009] The purpose of the present invention is to provide a halogen-free flame retardant masterbatch and a preparation method thereof and a high-strength halogen-free flame retardant injection plastic. By using bis(4-carboxyphenyl)phenylphosphine oxide as a chain extender, a flame retardant is introduced into a polyurethane structure, and the halogen-free flame retardant masterbatch prepared by melt extrusion with a flame retardant carrier has a high melt index, good fluidity and good processing performance; by adjusting the type of polyol and the type of diisocyanate and controlling the molar ratio, the tensile strength of the prepared halogen-free flame retardant masterbatch is increased; by adding a plasticizer, adjusting the type and amount of the plasticizer, and controlling the amount of the halogen-free flame retardant masterbatch, the impact strength of the prepared halogen-free flame retardant injection plastic is improved; by using modified graphene to load the halogen-free flame retardant, the heat resistance of the prepared halogen-free flame retardant injection plastic is improved; by using the halogen-free flame retardant masterbatch and the flame retardant synergist in synergistic use, the flame retardant performance of the prepared injection plastic is improved.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] In one aspect, the present invention provides a method for preparing a halogen-free flame retardant masterbatch, wherein the preparation of the halogen-free flame retardant masterbatch comprises the following steps:
[0012] The diisocyanate and the polyol are dried in a vacuum drying oven at 80° C. for 2 hours to obtain a dry raw material; the polyol and the diisocyanate are added into a four-necked flask and dissolved in DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., and 1% dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; 20-35 parts of bis(4-carboxyphenyl)phenylphosphine oxide are added to the reaction system, and the reaction is carried out at 50° C. for chain extension reaction for 2 hours to obtain a flame retardant prepolymer;
[0013] Weigh 10-25 parts of epoxy resin E52, dissolve the epoxy resin in 60 mL of toluene to obtain a resin solution; add triethylamine and KH-792 to the resin solution to obtain a reaction solution; adjust the pH value of the reaction solution to 5, heat it to 90° C., heat and stir it for 5 hours to obtain a polymer; vacuum dry the polymer at 80° C. for 2 hours to obtain a flame retardant carrier;
[0014] 15-25 parts of the flame retardant carrier, 60-90 parts of the flame retardant prepolymer, 5 parts of polyethylene wax, 10 parts of phenyl o-hydroxybenzoate, and 10105 parts of an antioxidant are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending and melt extrusion to obtain the halogen-free flame retardant masterbatch.
[0015] The molar ratio of the diisocyanate to the polyol is 1-1.8:1.
[0016] Preferably, the structural formula of the bis(4-carboxyphenyl)phenylphosphine oxide is as follows:
[0017]
[0018] Preferably, the diisocyanate is selected from toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and terephthalylidene diisocyanate.
[0019] Preferably, the polyol is selected from one of polyether diol, polytetramethylene glycol, polycaprolactone diol and polypropylene glycol.
[0020] Another aspect of the present invention provides a method for preparing a high-strength halogen-free flame-retardant injection plastic, characterized in that the high-strength halogen-free flame-retardant injection plastic comprises the following preparation steps:
[0021] The halogen-free flame retardant masterbatch, PA66, plasticizer, antioxidant 1010, and flame retardant synergist are added to a high-speed mixer and mixed evenly to obtain a mixed material; the mixed material is added to a twin-screw extruder for blending, melting and extrusion, and cooled and pelletized to obtain an extrusion material; the extrusion material is vacuum dried at 85° C. for 5 hours, and the high-strength halogen-free flame retardant injection molding material is obtained by injection molding with an injection molding machine;
[0022] The flame retardant synergist is prepared by modifying graphene with a silane coupling agent to obtain modified graphene, and the modified graphene is prepared by loading magnesium hydroxide and triphenyl phosphate.
[0023] Preferably, the plasticizer is selected from one of dioctyl phthalate, ethylene-vinyl acetate copolymer, nitrile rubber, and phenyl o-hydroxybenzoate.
[0024] Preferably, the preparation of the flame retardant synergist comprises the following steps:
[0025] The graphene is added to a three-necked flask, and a mixed solution of ethanol and water (V alcohol: V water = 5:1) is added to dissolve to obtain a mixed solution; the mixed solution is adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, the silane coupling agent is added, and the modified graphene is stirred for reaction under 85° C. water bath conditions for 6 hours to obtain the modified graphene; the modified graphene is dispersed in distilled water, ultrasonically dispersed for 20 minutes, the magnesium hydroxide is added, and the ultrasonication is continued for 20 minutes, ammonia water is added, the pH is adjusted to 9.5, and the mixture is allowed to stand for 1 hour, and the precipitate is filtered and washed to obtain a mixture; deionized water is added to the mixture, dispersed evenly, reacted at 180° C. for 5 hours, separated and centrifuged, washed and dried to obtain a premix; the premix is mixed with the triphenyl phosphate, the temperature is raised to 80° C., reacted for 2 hours, and filtered and washed to obtain the flame retardant synergist.
[0026] Preferably, the operating parameters of the twin-screw extruder are: a screw speed of 300 r / min, a feed speed of 25 r / min, the temperatures from the first temperature zone to the eighth temperature zone are: 210°C, 215°C, 220°C, 225°C, 230°C, 230°C, 220°C, 215°C, and the head temperature is 205°C.
[0027] Preferably, the working parameters of the injection molding machine are as follows: the temperatures of zones 1 to 3 are 210° C., 215° C., and 220° C., respectively, the nozzle temperature is 210° C.; the holding time is 15 s, the cooling time is 20 s, and the holding pressure is 120 MPa.
[0028] Preferably, the silane coupling agent is selected from one of KH-550, KH-560, KH-570 and KH-792; and the amount of the silane coupling agent is 1-8 parts.
[0029] Preferably, the ratio of the modified graphene, the magnesium hydroxide and the triphenyl phosphate in the flame retardant synergist is 10:1-4:1-4; and the amount of the modified graphene is 8-25 parts.
[0030] Preferably, the high-strength halogen-free flame-retardant injection molding material comprises 10-30 parts of halogen-free flame-retardant masterbatch, 100 parts of PA66, 5-10 parts of plasticizer, 10-20 parts of flame-retardant synergist, and 10-105 parts of antioxidant.
[0031] The invention provides a high-strength halogen-free flame-retardant injection plastic, which comprises a halogen-free flame-retardant masterbatch, PA66, a plasticizer, a flame-retardant synergist, and an antioxidant; the halogen-free flame-retardant masterbatch is prepared by the preparation method as described above; the high-strength halogen-free flame-retardant injection plastic is prepared by the preparation method as described above; the halogen-free flame-retardant masterbatch in the high-strength halogen-free flame-retardant injection plastic has a 180°C melt index of 19.6 g / 10 min; the halogen-free flame-retardant masterbatch in the high-strength halogen-free flame-retardant injection plastic has a tensile strength of 75.8 MPa and an elongation at break of 68.3%; the impact strength of the high-strength halogen-free flame-retardant injection plastic is 6.4 MPa; the initial decomposition temperature of the high-strength halogen-free flame-retardant injection plastic is 356°C, and the residual carbon rate is 41.2%; the limiting oxygen index of the high-strength halogen-free flame-retardant injection plastic is 32.5%, and the carbonization rate is 6.8%.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The present invention forms polyurethane by reacting diisocyanate with polyol, uses bis(4-carboxyphenyl)phenylphosphine oxide as a chain extender, prepares a flame retardant prepolymer, reacts a silane coupling agent with epoxy resin E52 to prepare a flame retardant carrier, extrudes and granulates the flame retardant prepolymer and the flame retardant carrier with a twin-screw extruder to prepare a halogen-free flame retardant masterbatch, controls the amount of components, and adjusts the processability of the halogen-free flame retardant masterbatch. The 180°C melt index of the prepared halogen-free flame retardant masterbatch is 19.6 g / 10 min, showing significantly improved fluidity and good processability.
[0034] 2. The present invention controls the types of polyols and diisocyanates, adjusts the molar ratio of diisocyanates to polyols, and utilizes long-chain isocyanates to effectively reduce the acting force. The applied stress can be dispersed in the fatty straight chain, thereby increasing the tensile strength of the flame retardant masterbatch. At the same time, the introduction of ether bonds improves the elongation at break of the masterbatch. The tensile strength of the prepared halogen-free flame retardant masterbatch is 75.8 MPa, and the elongation at break is 68.3%, showing significantly improved tensile properties.
[0035] 3. The present invention controls the amount of halogen-free flame retardant masterbatch, the type and amount of plasticizer, and utilizes the addition of plasticizer to induce silver streaks and shear bands. The generation and development of silver streaks and shear bands consume a lot of energy, thereby improving the strength of the injection molding material. At the same time, the flame retardant component is embedded in the macromolecular chain of the flame retardant masterbatch in the form of chemical bonds, thereby improving the compatibility. The obtained high-strength halogen-free flame retardant injection molding material has an impact strength of 6.4 MPa, showing significantly improved mechanical strength.
[0036] 4. The present invention uses a flame retardant synergist to cooperate with the flame retardant masterbatch to improve the flame retardant performance. At the same time, the modified graphene is used as a matrix. Its high surface area and special crystal structure can load the halogen-free flame retardant to avoid the rapid decomposition of the flame retardant at high temperatures, thereby improving the heat resistance of the injection molding material. The obtained high-strength halogen-free flame retardant injection molding material has an initial decomposition temperature of 356°C and a residual carbon rate of 41.2%, showing significantly improved heat resistance.
[0037] 5. The present invention uses halogen-free flame retardant masterbatch and flame retardant synergist in a coordinated manner, controls the dosage, and utilizes phosphorus and nitrogen to produce strong dehydrating products such as phosphoric acid and polyphosphoric acid, which prevents the material from continuing to burn. At the same time, groups such as benzene rings in the halogen-free flame retardant masterbatch will play the role of carbonizing agent when the polymer burns, promoting the formation of a dark and thick coke layer; the obtained high-strength halogen-free flame retardant injection molding material has a limiting oxygen index of 32.5% and a carbonization rate of 6.8%, showing significantly improved flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is the thermogravimetric curve diagram of Examples 37-40 of the present invention and Comparative Examples 6-7. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] See also Figure 1 The present invention provides a halogen-free flame-retardant masterbatch and a preparation method thereof and a high-strength halogen-free flame-retardant injection molding material. The technical scheme is as follows:
[0041] The KH-550 described in the present invention is 3-aminopropyltriethoxysilane, CAS: 919-30-2.
[0042] The KH-560 described in the present invention is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, CAS: 2530-83-8.
[0043] The KH-570 described in the present invention is methacryloxypropyltriethoxysilane, CAS: 2530-85-0.
[0044] The KH-792 described in the present invention is N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, CAS: 1760-24-3.
[0045] Example 1
[0046] Preparation of halogen-free flame retardant masterbatch:
[0047] Toluene diisocyanate and polytetrahydrofuran diol are dried at 80° C. for 2 hours in a vacuum drying oven to obtain a dry raw material; the polytetrahydrofuran diol and the toluene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., 1% of a catalyst dibutyltin dilaurate is added and reacted for 3 hours to obtain a reaction system; 30 parts of bis(4-carboxyphenyl)phenylphosphine oxide are added into the reaction system as a chain extender, and the reaction is carried out at 50° C. for a chain extension reaction to obtain a flame retardant prepolymer.
[0048] Weigh 20 parts of epoxy resin E52, dissolve the epoxy resin in 60 mL of toluene to obtain a resin solution; add 15 mL of triethylamine and 2 parts of silane coupling agent KH550 to the resin solution and add them to the mixed solution to form a reaction solution; adjust the pH value of the reaction solution to 5, heat it to 90° C., heat and stir for 5 hours to obtain a polymer; vacuum dry the polymer at 80° C. for 2 hours to obtain a flame retardant carrier;
[0049] 20 parts of the flame retardant carrier, 80 parts of the flame retardant prepolymer, 5 parts of polyethylene wax, 10 parts of phenyl o-hydroxybenzoate, and 10105 parts of the antioxidant are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending and melt extrusion to obtain the halogen-free flame retardant masterbatch.
[0050] Examples 2-12 refer to the preparation methods and parameter conditions of Example 1, with the differences shown in Table 1.
[0051] Table 1 Component dosage of Examples 1-12
[0052]
[0053]
[0054] Comparative Example 1 refers to the preparation method and parameter conditions of Example 1, except that no epoxy resin is added.
[0055] Comparative Example 2 refers to the preparation method and parameter conditions of Example 1, except that no silane coupling agent is added.
[0056] Example 13 Fluidity Test
[0057] The halogen-free flame retardant masterbatch prepared in Examples 1-12 and Comparative Examples 1-2 was tested for its flow properties. The flow properties were characterized by the melt index, which is the mass of the melt flowing out every 10 minutes. The melt index was tested using a melt index tester (Mpxrz-400) at a test temperature of 180°C. The test results are shown in Table 2.
[0058] Table 2 Fluidity test of Examples 1-12 and Comparative Examples 1-2
[0059]
[0060]
[0061] The results in Table 2 show that the melt index of the halogen-free flame-retardant masterbatch prepared by not adding epoxy resin in Comparative Example 1 and not adding epoxy resin modified by silane coupling agent in Comparative Example 2 shows a significant decrease compared with Examples 1-12, and the fluidity becomes worse, and the extrusion is unstable during the subsequent processing, which further affects the flame retardant properties of the material; the results of Examples 1-3 show that changing the type of silane coupling agent has little effect on the melt index of the flame retardant masterbatch, and the use of a silane coupling agent containing a polar group can increase the compatibility of the flame retardant carrier with the flame retardant prepolymer, and the flame retardant masterbatch obtained by extrusion granulation has better processing performance; the results of Examples 3-9 show that with the increase in the amount of flame retardant prepolymer, the melt index shows a trend of first increasing and then decreasing. The polyurethane group is introduced into the material, and the flame retardant carrier is grafted and polymerized during the melt extrusion process, and the viscosity of the flame retardant masterbatch is improved. The excessive flame retardant prepolymer and the flame retardant carrier enhance the intermolecular force of the halogen-free flame retardant masterbatch, increase the melting temperature of the masterbatch, reduce the melt index, and the viscosity is too large, which is not conducive to the uniform dispersion of the flame retardant in the halogen-free flame retardant masterbatch, and reduce the processing performance and flame retardant performance of the masterbatch; the results of Example 3 and Example 10-12 show that with the increase of the epoxy resin content, the melt index of the halogen-free flame retardant masterbatch increases first and then decreases. The epoxy resin and the silane coupling agent work synergistically, and they are cross-linked with the flame retardant prepolymer molecular chain, thereby increasing the uniform fluidity of the masterbatch. However, the excessive epoxy resin increases the viscosity of the masterbatch and reduces the processing performance. It can be seen from the results of Table 2 that the 180°C melt index of the halogen-free flame retardant masterbatch is 19.6g / 10min by controlling the amount of the flame retardant prepolymer and the flame retardant carrier, showing significantly improved fluidity and excellent processing performance.
[0062] Examples 14-23 refer to the preparation methods and parameter conditions of Example 3, with the differences shown in Table 3.
[0063] Comparative Example 3 refers to the preparation method and parameter conditions of Example 1, except that no flame retardant carrier is added.
[0064] Example 24 Tensile Properties Test
[0065] The halogen-free flame retardant masterbatch prepared in Examples 14-23 and Comparative Example 3 was subjected to tensile performance test using a universal mechanical testing machine (XWW-20A) to test the tensile strength and elongation at break of the material. The test was carried out in accordance with GB / T228.1-2010. During the test, the test specimen was stably fixed with a clamping specimen, and the tensile rate was set to 20 mm / min. The test results are shown in Table 3.
[0066] Table 3 Tensile performance test of Examples 14-23 and Comparative Example 3
[0067]
[0068]
[0069] From the results in Table 3, it can be seen that in Comparative Example 3, no epoxy resin was added to prepare the flame retardant carrier, and the tensile strength and elongation at break of the obtained halogen-free flame retardant masterbatch were significantly reduced compared with those of Examples 14-23. By using silane coupling agent for modification, the compatibility was improved, and the fluidity of the halogen-free flame retardant masterbatch was increased. At the same time, the polar groups contained in the epoxy resin can cross-link with the isocyanate polar groups in the flame retardant prepolymer to form a stable intermolecular force, thereby improving the tensile properties of the halogen-free flame retardant masterbatch. From the results in Examples 14-17, it can be seen that the flame retardant masterbatch prepared using hexamethylene diisocyanate has significantly improved tensile strength and elongation at break. Long-chain isocyanates can effectively reduce the force, and the applied stress can be dispersed in the fatty straight chain, so that the tensile strength of the flame retardant masterbatch is increased. At the same time, the dispersed force can increase the ductility of the masterbatch and improve the elongation at break. Aromatic isocyanates and alicyclic isocyanates have a rigid ring structure. , the tensile strength of the masterbatch can be increased, but due to the conjugation effect, the applied external force further enhances the intermolecular force in the structural system, and the elongation at break is reduced; the results of Examples 17-20 show that the use of ether bonds increases the flexibility in the main chain of the masterbatch molecule, improves the tensile strength and elongation at break of the masterbatch, but the introduction of rigid groups reduces the elongation at break of the masterbatch; the results of Examples 17 and 21-23 show that with the increase of the molar ratio of diisocyanate to polyol, the tensile strength and elongation at break of the flame retardant masterbatch gradually increase. When the molar ratio is 1.5:1, the tensile strength and elongation at break increase slowly, and the mechanical properties of the masterbatch tend to be stable; from the results of Table 3, it can be seen that by using polyether diol and hexamethylene diisocyanate, and controlling the molar ratio of diisocyanate to polyol, the halogen-free flame retardant masterbatch obtained has a tensile strength of 75.8 MPa and an elongation at break of 68.3%, showing significantly improved tensile properties.
[0070] Embodiment 25
[0071] 40 parts of hexamethylene diisocyanate and 30 parts of polyether diol are dried in a vacuum drying oven at 80°C for 2 hours to obtain a dry raw material; the polyether diol and the hexamethylene diisocyanate are added into a four-necked flask and dissolved in 2 ml of DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50°C, and 1% of a catalyst dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; 30 parts of bis(4-carboxyphenyl)phenylphosphine oxide are added to the reaction system as a chain extender, and the reaction is carried out at 50°C for chain extension reaction for 2 hours to obtain a flame retardant prepolymer.
[0072] Weigh 20 parts of epoxy resin, dissolve the epoxy resin in 60 mL of toluene to obtain a resin solution; add 15 mL of triethylamine and 2 parts of silane coupling agent KH-792 to the resin solution and add them to the mixed solution to form a reaction solution; adjust the pH value of the reaction solution to 5, heat it to 90° C., heat and stir for 5 hours to obtain a polymer; vacuum dry the polymer at 80° C. for 2 hours to obtain a flame retardant carrier;
[0073] 20 parts of the flame retardant carrier, 80 parts of the flame retardant prepolymer, 5 parts of polyethylene wax, 10 parts of phenyl o-hydroxybenzoate, and 10105 parts of the antioxidant are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending and melt extrusion to obtain a halogen-free flame retardant masterbatch.
[0074] 20 parts of the halogen-free flame retardant masterbatch, 100 parts of PA66, 8 parts of plasticizer, 10105 parts of antioxidant, and 10 parts of flame retardant synergist are added into a high-speed mixer and mixed evenly to obtain a mixture; the mixture is added into a twin-screw extruder for blending, melt extrusion, cooling, and pelletizing to obtain an extrudate; the extrudate is vacuum dried at 85°C for 5 hours and then injection molded by an injection molding machine to obtain the high-strength halogen-free flame retardant injection molding material.
[0075] Examples 26-35 refer to the preparation method and parameter conditions of Example 25, and the differences are shown in Table 4.
[0076] Comparative Example 4 refers to the preparation method and parameter conditions of Example 25, except that no plasticizer is added.
[0077] Comparative Example 5 refers to the preparation method and parameter conditions of Example 25, except that halogen-free flame retardant masterbatch is not used and an equal amount of flame retardant synergist is added.
[0078] Example 36 Impact Performance Test
[0079] The high-strength halogen-free flame-retardant injection molding materials prepared in Examples 25-35 and Comparative Example 4 were subjected to impact strength tests using an impact testing machine (XJ-300A) according to the national standard GB / T1043.1-2008. Before impact, the prepared standard test specimens were stably fixed with a fixture, and the pendulum of the impact testing machine was dropped at an angle of 150° during impact. The test results are shown in Table 4.
[0080] Table 4 Impact performance test of Examples 25-35 and Comparative Example 4
[0081]
[0082]
[0083] The results in Table 4 show that the impact strength of the high-strength halogen-free flame-retardant injection molding compound obtained without adding plasticizer in Comparative Example 4 is significantly reduced. The addition of plasticizer can induce silver streaks and shear bands. The generation and development of silver streaks and shear bands consume a lot of energy, which improves the strength of the injection molding compound. Compared with Examples 25-35, the impact strength of the injection molding compound without adding flame-retardant masterbatch in Comparative Example 5 is significantly improved. The addition of flame-retardant masterbatch reduces the impact strength of the injection molding compound. This is mainly because the flame-retardant masterbatch containing macromolecular groups such as benzene rings is mixed with PA66 for melt crystallization, which promotes the molecular structure of the final product. The rigidity of the chain increases. When it is subjected to external impact force, the rigid chain segment is forcibly broken before it can adjust the spatial displacement, resulting in a decrease in impact strength. However, the flame retardant component is embedded in the macromolecular chain of the flame retardant masterbatch in the form of a chemical bond, becoming a part of the macromolecular chain of the flame retardant masterbatch, and will not affect the compatibility between the flame retardant masterbatch and PA66. The polar groups provided by the epoxy resin increase the intermolecular force, so the effect on the mechanical properties is small. PA66 has a low limiting oxygen index and poor flame retardant properties. The addition of flame retardant masterbatch can improve the flame retardant properties of injection molding plastics. The results of Examples 25-28 show that with the increase in the amount of halogen-free flame retardant masterbatch, the impact strength of the injection molding compound gradually decreases. When the amount of halogen-free flame retardant masterbatch is greater than 20 parts, the impact strength of the injection molding compound is greatly reduced. The results of Examples 25 and 30-32 show that when phenyl ester plasticizers are used, the impact strength of the injection molding compound can reach more than 6MPa. The results of Examples 25 and 33-35 show that with the increase in the amount of plasticizer, the impact strength of the injection molding compound shows a trend of first increasing and then decreasing. With the increase in the amount of plasticizer, the silver grain branching and shear band effect reach saturation, and the toughening effect gradually slows down. Excessive plasticizers will reduce the compatibility of the injection molding compound, resulting in a decrease in impact strength. From the results of Table 4, it can be seen that when dioctyl phthalate is used as a plasticizer and the amount of plasticizer is controlled to 8 parts, the impact strength of the high-strength halogen-free flame retardant injection molding compound is 6.4MPa, showing a significantly improved mechanical strength.
[0084] Embodiment 37
[0085] Preparation of flame retardant synergist:
[0086] 50 parts of graphene are added to a three-necked flask, and 100 ml of a mixed solution of ethanol and water (V alcohol: V water = 5:1) is dissolved to obtain a mixed solution; the mixed solution is adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, 5 parts of silane coupling agent are added, and the modified graphene is stirred for reaction under 85° C. water bath conditions for 6 hours to obtain the modified graphene; 20 parts of the modified graphene are dispersed in distilled water, ultrasonically dispersed for 20 minutes, 2 parts of magnesium hydroxide are added, and the ultrasonication is continued for 20 minutes, ammonia water is added, the pH is adjusted to 9.5, and the mixture is allowed to stand for 1 hour, and the precipitate is filtered and washed to obtain a mixture; deionized water is added to the mixture, dispersed evenly, reacted at 180° C. for 5 hours, separated and centrifuged, washed and dried to obtain a premix; the premix is mixed with 8 parts of triphenyl phosphate, heated to 80° C., reacted for 2 hours, and filtered and washed to obtain a flame retardant synergist.
[0087] The preparation of high-strength halogen-free flame-retardant injection molding material is prepared by referring to Example 25.
[0088] Examples 38-46 refer to the preparation method and parameter conditions of Example 37, and the differences are shown in Table 5.
[0089] Comparative Example 6 refers to the preparation method and parameter conditions of Example 37, except that graphene oxide is not added, and only a mixture of magnesium hydroxide and triphenyl phosphate in a ratio of 1:4 is added.
[0090] Comparative Example 7 refers to the preparation method and parameter conditions of Example 37, except that unmodified graphene oxide is added.
[0091] Example 47 Heat resistance performance measurement
[0092] The high-strength halogen-free flame-retardant injection molding materials prepared in Examples 37-46 and Comparative Examples 6-7 were tested using 5 mg samples. The temperature rise rate was controlled to be 10°C / min by a thermogravimetric analyzer. The test temperature range was 25-600°C. As the test temperature increased, the initial decomposition temperature and the residual carbon rate were recorded. The thermogravimetric curves of Examples 37-40 and Comparative Examples 6-7 are shown in FIG. Figure 1 The test results are shown in Table 5.
[0093] Table 5 Determination of heat resistance of Examples 37-46 and Comparative Examples 6-7
[0094]
[0095] pass Figure 1The results show that the heat resistance of Examples 37-40 is significantly improved compared with that of Comparative Examples 6-7, and the initial decomposition temperature and the residual carbon rate are significantly improved; the results in Table 5 show that in Comparative Example 6, no graphene oxide is added, and only a mixture of magnesium hydroxide and triphenyl phosphate in a ratio of 1:4 is added as a flame retardant synergist, and the heat resistance of the obtained high-strength halogen-free flame retardant injection plastic is poor. Since magnesium hydroxide and triphenyl phosphate are easily decomposed at high temperatures, the generated gases volatilize, which reduces the flame retardant properties of the injection plastic, and the flame retardant properties further decrease during high-temperature combustion; in Comparative Example 7, graphene modified with a silane coupling agent is not used, and the initial decomposition temperature and the residual carbon rate are significantly improved compared with those of Comparative Example 6. However, the initial decomposition temperature of the high-strength halogen-free flame retardant injection plastic obtained by Examples 37-46 reaches above 300°C, showing significantly improved heat resistance. The addition of silane coupling agent improves the compatibility of the flame retardant synergist with the injection plastic and improves the heat resistance; From the results of Examples 37-40, it can be seen that KH-792 forms a silanol structure under acidic conditions, which can bond with the graphene surface. At the same time, the polar group at the other end can undergo graft polymerization with PA66, thereby improving the compatibility between the components of the injection molding plastic. However, the ethoxy groups contained in other silane coupling agents have poor hydrolysis performance, weakened ability to bind with graphene, reduced compatibility of the components of the injection molding plastic, and poor heat resistance. From the results of Examples 40-46, it can be seen that with the increase in the amount of KH-792 and modified graphene, the initial decomposition temperature of the injection molding plastic shows a trend of increasing and then decreasing. An appropriate amount of modified graphene as a matrix, with its high surface area and special crystal structure, can load magnesium hydroxide and triphenyl phosphate flame retardants, promote flame conduction and heat release, thereby achieving a flame retardant effect. At the same time, loading the halogen-free flame retardant can avoid rapid decomposition of the flame retardant at high temperatures, avoid reduced flame retardancy due to excessively high temperatures, and improve the heat resistance of the injection molding plastic. Comprehensive Table 5, Figure 1 The results show that the high-strength halogen-free flame-retardant injection molding material prepared by using KH-792-modified graphene-loaded magnesium hydroxide and triphenyl phosphate flame retardant synergist has an initial decomposition temperature of 356°C and a residual carbon rate of 41.2%, showing significantly improved heat resistance.
[0096] Examples 48-59 refer to the preparation method and parameter conditions of Example 40, and the differences are shown in Table 6.
[0097] Table 6 Differences in the amount of components used in Examples 48-59
[0098]
[0099] Comparative Example 8 refers to the preparation method and parameter conditions of Example 40, except that no halogen-free flame retardant masterbatch is added.
[0100] Comparative Example 9 refers to the preparation method and parameter conditions of Example 40, except that no flame retardant synergist is added.
[0101] Example 60 Flame retardant performance test
[0102] Carbonization rate: The high-strength halogen-free flame-retardant injection molding materials prepared in Examples 48-59 and Comparative Examples 8-9 were made into test specimens. During the experiment, the mass of the crucible used, the mass of the tested sample, and the total weight of the residual carbon and the crucible after the sample was completely burned were accurately weighed. The crucible containing the tested sample was placed in a muffle furnace at 800°C and completely burned, and the carbonization rate was calculated;
[0103] Limiting oxygen index: The limiting oxygen index was determined on a LOI instrument (K-R2406S) using the standard test method of AMSD D286. The test results are shown in Table 7.
[0104] Table 7 Flame retardant test of Examples 48-59 and Comparative Examples 8-9
[0105] Example Limiting oxygen index / % Carbonization rate / % Embodiment 48 32.5 6.8 Embodiment 49 30.8 5.6 Embodiment 50 31.5 6.2 Embodiment 51 31.9 6.5 Embodiment 52 28.2 4.8 Embodiment 53 29.6 5.2 Embodiment 54 31.4 6.1 Embodiment 55 29.8 5.2 Embodiment 56 31.1 5.9 Embodiment 57 33.8 7.2 Embodiment 58 31.5 6.3 Embodiment 59 32.8 7.0 Comparative Example 8 25.8 0.8 Comparative Example 9 27.2 4.6
[0106] From the results in Table 7, it can be seen that the limiting oxygen index of the injection molding material obtained in Comparative Example 8 without adding the halogen-free flame retardant masterbatch is 25.8%, and the carbonization rate is only 0.8%. Since magnesium hydroxide and triphenyl phosphate mainly prevent the continuous combustion by releasing non-flammable gas, they can no longer form a dense carbon layer to prevent further combustion. Compared with Comparative Example 9, the flame retardant performance of the injection molding material without adding the flame retardant synergist is increased, but compared with Examples 47-59, the flame retardant performance needs to be improved. The results of Examples 48-50 show that the change The ratio of modified graphene, magnesium hydroxide, and triphenyl phosphate has little effect on the flame retardant properties. However, the addition of excessive inorganic hydroxides will reduce the compatibility between the components of the injection molding compound and increase the possibility of agglomeration. The results of Examples 48 and 51-53 show that with the increase in the amount of bis(4-carboxyphenyl)phenylphosphine oxide, the flame retardant properties of the injection molding compound show a trend of first increasing and then decreasing. Due to the preparation of halogen-free flame retardant masterbatch, flame retardant elements such as phosphorus, nitrogen, and carbon are introduced into the chain structure to increase the flame retardant properties. However, excessive The addition of bis(4-carboxyphenyl)phenylphosphine oxide introduces an excessive amount of rigid benzene ring structure, which reduces the mechanical properties of the injection molding compound. The results of Examples 48 and 54-56 show that as the amount of halogen-free flame retardant masterbatch increases, the flame retardant properties of the injection molding compound gradually improve, and the limiting oxygen index and the charring rate gradually increase. Since the halogen-free flame retardant masterbatch contains flame retardant elements such as phosphorus, nitrogen, and carbon, during the heating process, phosphorus and nitrogen will react chemically to produce strong dehydrating products such as phosphoric acid and polyphosphoric acid, resulting in the removal of water from PA66 to form char. Carbon-like substance, this coke covers the surface of the polymer matrix, causing the material to be unable to continue burning. At the same time, the benzene ring and other groups in the halogen-free flame retardant masterbatch will play the role of a carbonizing agent when the polymer burns, prompting the formation of a dark and thick coke layer, improving the flame retardant effect. However, according to the results of Table 4, the addition of excessive halogen-free flame retardant masterbatch will reduce the mechanical properties of the injection molding material; the results of Examples 48 and 57-59 show that with the increase in the amount of flame retardant synergist, the limiting oxygen index and the carbonization rate gradually increase and tend to remain unchanged. From the results of Table 7, it can be seen that by controlling the amount of halogen-free flame retardant masterbatch and the amount of flame retardant synergist, the high-strength halogen-free flame retardant injection molding material has a limiting oxygen index of 32.5% and a carbonization rate of 6.8%, showing significantly improved flame retardant properties.
[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a halogen-free flame retardant masterbatch, characterized in that: The preparation of the halogen-free flame retardant masterbatch comprises the following steps: The diisocyanate and the polyol are dried at 80° C. for 2 hours in a vacuum drying oven to obtain a dry raw material; the polyol and the diisocyanate are added into a four-necked flask and dissolved in DMF to obtain a dissolving system; the dissolving system is protected by nitrogen, heated to 50° C., and dibutyltin dilaurate is added to react for 3 hours to obtain a reaction system; 20-35 parts of bis(4-carboxyphenyl)phenylphosphine oxide are added to the reaction system, and the reaction is carried out at 50° C. for chain extension reaction for 2 hours to obtain a flame retardant prepolymer; Weigh 10-25 parts of epoxy resin E52, dissolve the epoxy resin in 60 mL of toluene to obtain a resin solution; add triethylamine and silane coupling agent to the resin solution to obtain a reaction solution; adjust the pH value of the reaction solution to 5, heat it to 90° C., heat and stir for 5 hours to obtain a polymer; vacuum dry the polymer at 80° C. for 2 hours to obtain a flame retardant carrier; Add 15-25 parts of the flame retardant carrier, 60-90 parts of the flame retardant prepolymer, 5 parts of polyethylene wax, 10 parts of phenyl o-hydroxybenzoate, and 10-105 parts of an antioxidant into a high-speed mixer and mix them evenly to obtain a mixture; add the mixture into a twin-screw extruder for blending and melt extrusion to obtain the halogen-free flame retardant masterbatch; The molar ratio of the diisocyanate to the polyol is 1-1.8:
1.
2. The method for preparing a halogen-free flame retardant masterbatch according to claim 1, characterized in that: The diisocyanate is selected from toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and terephthalylidene diisocyanate.
3. The method for preparing a halogen-free flame retardant masterbatch according to claim 1, characterized in that: The polyol is selected from one of polyether glycol, polytetramethylene glycol, polycaprolactone glycol and polypropylene glycol.
4. A method for preparing a high-strength halogen-free flame-retardant injection molding material, characterized in that: The high-strength halogen-free flame-retardant injection molding material comprises the following preparation steps: The halogen-free flame retardant masterbatch, PA66, plasticizer, antioxidant 1010, and flame retardant synergist are added to a high-speed mixer and mixed evenly to obtain a mixed material; the mixed material is added to a twin-screw extruder for blending, melting and extrusion, and cooled and pelletized to obtain an extrusion material; the extrusion material is vacuum dried at 85° C. for 5 hours, and the high-strength halogen-free flame retardant injection molding material is obtained by injection molding with an injection molding machine; The flame retardant synergist is prepared by modifying graphene with a silane coupling agent to obtain modified graphene; the modified graphene is prepared by loading magnesium hydroxide and triphenyl phosphate.
5. The method for preparing a high-strength halogen-free flame-retardant injection molding material according to claim 4, characterized in that: The plasticizer is selected from one of dioctyl phthalate, ethylene-vinyl acetate copolymer, nitrile rubber and phenyl o-hydroxybenzoate.
6. The method for preparing a high-strength halogen-free flame-retardant injection molding material according to claim 4, characterized in that: The preparation of the flame retardant synergist comprises the following steps: The graphene is added into a three-necked flask, and a mixed solvent of ethanol and water (V alcohol: V water = 5:1) is added to dissolve to obtain a mixed solution; the mixed solution is adjusted to weak acidity with glacial acetic acid, ultrasonically dispersed for 30 minutes, the silane coupling agent is added, and the modified graphene is obtained by stirring and reacting in a water bath at 85° C. for 6 hours; The modified graphene is dispersed in distilled water, ultrasonically dispersed for 20 minutes, the magnesium hydroxide is added, ultrasonication is continued for 20 minutes, ammonia water is added, the pH is adjusted to 9.5, and a precipitate is obtained by standing for 1 hour; the precipitate is filtered and washed to obtain a mixture; deionized water is added to the mixture, dispersed evenly, reacted at 180° C. for 5 hours, separated and centrifuged, washed and dried to obtain a premix; the premix is mixed with the triphenyl phosphate, the temperature is raised to 80° C., reacted for 2 hours, filtered and washed to obtain the flame retardant synergist.
7. The method for preparing a high-strength halogen-free flame-retardant injection molding material according to claim 4, characterized in that: The silane coupling agent is selected from one of KH-550, KH-560, KH-570 and KH-792; the dosage of the silane coupling agent is 1-8 parts.
8. The method for preparing a high-strength halogen-free flame-retardant injection molding material according to claim 4, characterized in that: The ratio of the modified graphene, the magnesium hydroxide and the triphenyl phosphate in the flame retardant synergist is 10:1-4:1-4; the amount of the modified graphene is 8-25 parts.
9. The method for preparing a high-strength halogen-free flame-retardant injection molding material according to claim 4, characterized in that: The high-strength halogen-free flame-retardant injection molding material comprises 10-30 parts of the halogen-free flame-retardant masterbatch, 100 parts of the PA66, 5-10 parts of the plasticizer, 10-20 parts of the flame-retardant synergist, and 10-105 parts of the antioxidant.
10. A high-strength halogen-free flame-retardant injection molding material, characterized in that: The high-strength halogen-free flame-retardant injection plastic comprises halogen-free flame-retardant masterbatch, PA66, plasticizer, flame retardant synergist, and antioxidant; the halogen-free flame-retardant masterbatch is prepared by the preparation method described in any one of claims 1 to 3; the high-strength halogen-free flame-retardant injection plastic is prepared by the preparation method described in any one of claims 4 to 9; the halogen-free flame-retardant masterbatch in the high-strength halogen-free flame-retardant injection plastic has a 180°C melt index of 19.6 g / 10 min; the halogen-free flame-retardant masterbatch in the high-strength halogen-free flame-retardant injection plastic has a tensile strength of 75.8 MPa and an elongation at break of 68.3%; the impact strength of the high-strength halogen-free flame-retardant injection plastic is 6.4 MPa; the initial decomposition temperature of the high-strength halogen-free flame-retardant injection plastic is 356°C, and the residual carbon rate is 41.2%; the limiting oxygen index of the high-strength halogen-free flame-retardant injection plastic is 32.5%, and the carbonization rate is 6.8%.
Citation Information
Patent Citations
Special halogen-free flame-retardant master batch for nylon and preparation method thereof
CN103627168A
Flame-retardant PVC masterbatch and its preparation method
CN109181156B
Cited By
10kV cable low-smoke halogen-free flame-retardant sheath material and preparation method thereof
CN122563203A
